Enhanced electromagnetic wave absorption performance of silane coupling agent KH550@Fe3O4 hollow nanospheres/graphene composites - Shu, Xiangfeng; Ren, Hengdong; Jiang, Yu; Zhou, Jun; Wang, Yueqin; Wang, Yanfen; Liu, Yin; Won-Chun, Oh (Journal of materials chemistry. C, Materials for optical and electronic devices, 2020)
Monodisperse Fe3O4 hollow nanospheres with two sizes of ∼300 nm and ∼400 nm were modified by a silane coupling agent KH550 and then bonded with rGO via a hydrothermal route to obtain the composites. The main challenges in the preparation of Fe3O4/rGO composites are the dispersion of magnetic nanoparticles and their adhesion to the rGO flexible substrate. Therefore, in order to further promote the dispersion and adhesion of composites, the silane coupling agent KH550 is selected as a surface modifier for Fe3O4 to increase the hydrophobicity. The KH550@Fe3O4/rGO (KF/rGO) composites exhibit enhanced electromagnetic wave (EMW) absorption performance due to the improvements of their permittivity and impedance matching. A maximum RL value of −57.87 dB at 14.96 GHz from 13.1 GHz to 17.6 GHz is achieved by the KH550@Fe3O4/rGO composite with the mass ratio of KH550@Fe3O4 to GO being 1 : 1 (KF1-2). In particular, the thickness is only 1.48 mm, demonstrating the ultra-thin and high-intensity EMW absorption capability. This special core–shell/coating structure can be used for devising new and effective applications.